Implementation of Legal and Social Assistance for Street Children Victims of Sexual Exploitation in Padang City from the Perspective of Legal Sociology - Kamila Hesti; Danil, Elwi; Zurnetti, Aria (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2025)
Street children in Indonesia are among the most vulnerable social groups, particularly exposed to various forms of exploitation, including sexual abuse. Despite the existence of regulatory frameworks such as Law No. 35 of 2014 on Child Protection and local regulations in Padang City, the implementation of protective measures for these children remains inconsistent and fragmented. This study aims to investigate the implementation of assistance programs for street children who are victims of sexual exploitation, with a focus on the role played by the Padang City Social Service Office. The research also explores the legal and institutional challenges that hinder the effectiveness of such interventions. This research uses a juridical sociological approach with a qualitative method. Data was collected through in-depth interviews with government officials, social services, and other parties related to the research topic. Secondary data in the form of documents were obtained from literature studies of legal documents, policy reports, and academic literature. The findings indicate that while a framework for holistic support comprising legal aid, psychological counseling, education, and basic needs assistance has been established, its implementation suffers from several key constraints. These include limited government budgets, weak inter-agency coordination due to sectoral egotism, and a lack of public awareness regarding the rights and protection of child victims. Furthermore, social stigma often prevents effective community involvement. This study concludes that without strengthening social and institutional structures and increasing cross-sectoral synergies, child protection will not be effective. Strengthening policy implementation, public education, and integration of Islamic legal values such as the protection of the soul (ḥifẓ al-nafs) and descendants (ḥifẓ al-nasl) can be a strong normative basis in creating a fair and sustainable child protection system.